Modelling key reactive processes relevant to bisulfide transport through highly compacted bentonite - Md Abdullah Asad; Tarek L. Rashwan; Ian L. Molnar; Mehran Behazin; Peter G. Keech; Magdalena M. Krol (Results in Engineering)
The Canadian deep geological repository (DGR) design consists of copper coated used fuel containers (UFCs) placed within a highly compacted bentonite (HCB) buffer surrounded by a suitable host rock. Although the copper is thermodynamically stable in oxygen-free environments, it is potentially susceptible to microbiologically influenced corrosion from bisulfide (HS-). Therefore, understanding HS- corrosion is important to ensure long-term performance of UFCs. Various reactions in the bentonite barrier of the DGR can affect HS- transport through the HCB and therefore the extent of copper corrosion caused by HS-. Since HS- transport and reactive processes are interconnected, numerical models are required to assess the complex HS- reactive transport dynamics and quantify the influence of reactive processes on HS- transport and corrosion. In this paper, various HS- transport models were coupled with (i) a key geochemical reaction between HS- and iron (i.e., simulating HS- retardation due to iron sulfide formation) or (ii) HS- adsorption. Since HS- is an anion, anion exclusion was also explored. Valuable insight was obtained through validation, comparison, and sensitivity analyses of these models. A comparison between experimental and modelled HS- transport dynamics showed that HS- is being retained by the bentonite due to reactive processes and anion exclusion is occurring. Lastly, HS- transport was simulated for the entire DGR lifespan and was found to be delayed (≈50–800 years) due to FeS formation or HS- adsorption. However, these predicted HS- diffusion delays are relatively short in a DGR lifespan (i.e., 1 million years) and do not impact long-term HS- corrosion.